Evaluation of Serum Perforin, Caspase-3, sFasL and M-30 Levels as Apoptotic Markers in Children With Crimean-Congo Hemorrhagic Fever. Issue 2 (February 2015) - Güven, Ahmet S.; Sancakdar, Enver; Uysal, Elif B.; Kaya, Ali; Oflaz, Mehmet B.; Karapinar, Hekim; Bolat, Fatih; Tuzcu, Nevin; Deveci, Köksal; Cevit, Ömer; İcagasioglu, Füsun D.
<x xml:space="preserve">Abstract</x> Background: Apoptosis is a main regulator in responses of cellular immunity throughout systemic viral infections. Perforin, soluble Fas ligand, caspase-3 and caspase-cleaved cytokeratin-18 (M-30) are mediators of apoptosis. The aim of this study is the evaluation of Crimean-Congo hemorrhagic fever (CCHF) disease changes in the levels of these apoptotic markers and the relation of these changes with disease severity. Methods: Forty-nine hospitalized children with CCHF and 36 healthy controls were enrolled in this prospective study. The CCHF patients were classified into 2 groups based on disease severity (severe group and nonsevere group). Demographic characteristics and clinical and laboratory findings of all patients were recorded on admission. Results: Serum perforin, caspase-3 and soluble Fas ligand levels were found to be significantly higher both in the severe and nonsevere CCHF groups than the healthy control group (P < 0.05), but there was no significant difference in these apoptotic markers between severe and nonsevere CCHF groups (P > 0.05). In addition, serum M-30 levels did not differ significantly among all groups (P > 0.05). There was a positive correlation between serum values for perforin, caspase-3 and M-30 and the disease's severity criteria such as aspartate aminotransferase and/or alanine aminotransferase. The serum levels of all these markers were negatively correlated with disease severity criteria such as the platelet count. Conclusions: In this study, we concluded that the interactions of cytolytic granules containing perforin and caspase cascade and Fas-FasL may play an important role in the pathogenesis of CCHF in children.